2018
DOI: 10.1111/jop.12802
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of oral diffuse large B‐cell lymphoma, NOS: A systematic review

Abstract: Background Diffuse large B‐cell lymphoma, NOS (DLBCL NOS) is the commonest extranodal non‐Hodgkin lymphoma diagnosed in the oral and maxillofacial region. However, few studies are currently available and its prognostic determinants remain undefined. Purpose To analyse the available data on oral DLBCL NOS and to describe its clinicopathological features, identifying potential prognostic factors. Methods An electronic systematic search was performed using multiple databases with a specific search strategy in Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
5
21
1
Order By: Relevance
“…Early lesions are often attributed to inflammatory odontogenic or periodontal conditions. Other differential diagnosis to DLBCL in the oral cavity includes fibroma, pyogenic granuloma, pleomorphic adenoma, squamous cell carcinoma, soft tissue malignancies and minor salivary gland tumours. Furthermore, our patient did not complain of any B‐symptoms, which is the most common presentation.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Early lesions are often attributed to inflammatory odontogenic or periodontal conditions. Other differential diagnosis to DLBCL in the oral cavity includes fibroma, pyogenic granuloma, pleomorphic adenoma, squamous cell carcinoma, soft tissue malignancies and minor salivary gland tumours. Furthermore, our patient did not complain of any B‐symptoms, which is the most common presentation.…”
Section: Discussionmentioning
confidence: 76%
“…DLBCL NOS is a rare entity in the oral cavity. A systematic review published in 2018, analysing all published oral DLBCL NOS, revealed 63 publications comprising 122 cases – 31 of which were presented in the maxillary mucosa. In this specific case, endodontic treatment was performed prior to diagnosis, which resulted in a much later accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphomas represent about two thirds of hematologic diseases and involve 3.5% of all intra-oral malignant tumors [1]. There is a predominance among men and elderly population [2]. Two main types of lymphomas can be distinguished: Hodgkin's lymphoma and non-Hodgkin's lymphoma.…”
Section: Commentarymentioning
confidence: 99%